Quantifying mechanical loading during training in track atheltes - Moresi, M.; O'Meara, D.; Graham, K. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The present study investigated the potential of inertial sensors to objectively quantify mechanical load during training in track athletes. Three female sprinters wore a single inertial sensor attached to the distal tibia during identical training sessions on two separate occasions. Objective measures of the `relative` mechanical loading (acceleration integral expressed per second) obtained from the inertial sensors were highly correlated with increases in running velocity and indicated excellent repeatability across the two sessions. Quantifying mechanical loading during training using this technology appears viable and may provide important insights into differences in training loading within and between individuals. Such training load measures may assist in identifying increased injury risk in high level track and field athletes.